Optimalisasi Media Sosial untuk Promosi Hotel Bahtera Pelni Cipayung Bogor - Suci Rahmawati; Sri Harini (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2026)
The development of social media has become a crucial promotional strategy in the hospitality industry, including for Hotel Bahtera Pelni, located in Cipayung, Bogor. This study aims to analyze how the utilization of social media can be optimized as a promotional tool to enhance the hotel’s attractiveness, image, and marketing performance. The method applied in this research is qualitative descriptive, involving observations, interviews, and analysis of social media data. The results indicate that each platform has distinct audience characteristics and issues; for instance, Facebook requires particular attention to room cleanliness and facilities, Instagram highlights the efficiency of the check-in process, YouTube demands transparency regarding hotel amenities, while TikTok emphasizes the quality of service interactions. Optimizing social media, when combined with improvements in service quality, facilities, and prompt responses to customer complaints, has been shown to enhance the hotel’s image, customer satisfaction, and loyalty, while also supporting the achievement of revenue targets. This study underscores that digital promotion strategies should be integrated with professional operational management and human resources. These findings serve as a reference for developing measurable digital marketing strategies in the hospitality sector, ensuring that social media promotion is more effective and contributes to sustainable business performance improvement.